Identification of ventilated and submarine glacial meltwaters in the Amundsen Sea, Antarctica, using noble gases - Shin, DongYoub; Hahm, Doshik; Kim, Tae-Wan; Rhee, Tae Siek; Lee, SangHoon; Park, Keyhong; Park, Jisoo; Kwon, Young Shin; Kim, Mi Seon; Lee, Tongsup (Frontiers in Marine Science, 2022)
To delineate the glacial meltwater distribution, we used five noble gases for optimum multiparameter analysis (OMPA) of the water masses in the Dotson-Getz Trough (DGT), Amundsen Sea. The increased number of tracers allowed us to define potential source waters at the surface, which have not been possible with a small set of tracers. The highest submarine meltwater (SMW) fraction (∼0.6%) was present at the depth of ∼450 m near the Dotson Ice Shelf. The SMW appeared to travel beyond the continental shelf break along an isopycnal layer. Air-equilibrated freshwater (up to 1.5%), presumably ventilated SMW (VMW) and surface melts, was present in the surface layer (<100 m). The distribution of SMW indicates that upwelled SMW, known as an important carrier of iron to the upper layer, amounts for 29% of the SMW in the DGT. The clear separation of VMW from SMW enabled partitioning of meltwater into locally-produced and upstream fractions and estimation of the basal melting of 53 – 94 Gt yr−1 for the adjacent ice shelves, assuming that the SMW fractions represent accumulation since the previous Winter Water formation. The Meteoric Water (MET) fractions, consisting of SMW and VMW, comprised 24% of those derived from oxygen isotopes, indicating that the annual input from basal melting is far less than the inventory of meteoric water, represented by MET.